Fluorinated rhamnosides inhibit cellular fucosylation - Johan F. A. Pijnenborg (Nature Portfolio, 2021)
Aberrant expression of fucosylated glycans has been linked to several disease states. Control of fucose expression on live cells is needed to aid research and therapy development. Here the authors report on the development of a class of fucosylation metabolic prodrug inhibitors and demonstrated inhibition of cellular fucosylation.